C++ for engineers and scientist - Bronson, Gary J. (PWS Publishing, 1998)
With C++ gaining a stronghold in the engineering and scientific communities, Bronson's book makes C++ accessible to first level engineering students. Featuring a wealth of practical, engineering-oriented examples and applications, the book teaches the fundamentals of the C++ language with a gradual refinement of programming skills from a procedural to an object orientation.